ChemInform Abstract: Facile Synthesis of Indolizino[3, 4, 5‐ab]isoindoles by an Acid‐Induced Cyclization of 1, 2‐Di(1H‐pyrrol‐2‐yl)benzenes. Issue 2 (23rd December 2015) - Kuzuhara, Daiki; Miyake, Satoshi; Moriyama, Hirotake; Tamura, Yuto; Aratani, Naoki; Yamada, Hiroko
Abstract: The two‐step synthesis of the substrates via Suzuki‐coupling of the corresponding 1, 2‐dibromobenzene with N‐Boc‐pyrrole‐2‐boronic acid and subsequent N‐deprotection is described.